Peningkatan kapasitas vital paru pada wanita peserta senam aerobik di Bali - Ni Nyoman Yuni Wiastri; Suyasning Hastiko Indonesiani; Pande Ayu Naya Kasih Permatananda (MEDIA ILMU KESEHATAN, 2021)
Background: Aerobic exercise can increase cardiorespiratory endurance which is a major factor in physical fitness. By having a good lung vital capacity, a person has the body's ability to carry out activities without feeling tired.Objective: This study was aimed to determine the effect of mix impact aerobic exercise on the vital capacity of women’s lung.Methods: A quasy-experimental approach was conducted in this research with one group only pretest-posttest design. The subjects in this study were women aged 26-55 years, normal vital signs examination, not suffering from lung disease, and willing to participate in the whole series of research. Mixed impact aerobics as a treatment was given with a duration of 60 minutes and 3 times a week for 3 weeks and wash out period was given for one month. Spirometer was used to measure vital lung capacity.Results: There is an increase of vital lung capacity before and after the mix impact aerobic exercise of 0.09%. The results showed that there was an effect of mixed impact aerobic exercise on the vital capacity of the mothers' lungs (p < 0.05). Conclusion: There is a significant effect between mixed impact aerobics with vital lung capacity of women in Bali.